If I betray these words : moral injury in medicine and why it's so hard for clinicians to put patients first - Dean, Wendy; Talbot, Simon (Steerforth Press, 2023)
"Offering examples of how to make medicine better for the healers and those they serve, If I Betray These Words profiles clinicians across the country who are tough, resourceful, and resilient, but feel trapped between the patient-first values of their Hippocratic oath and the business imperatives of a broken healthcare system"--